The Effect of Elevated Basal Follicle Stimulating Hormone Levels on Assisted Reproductive Technology Cycle Outcomes - Kahyaoglu, Inci; Dogru, Hatice Yilmaz; Aksakal, Sezin Erturk; Kaplanoglu, Iskender; Dilbaz, Serdar; Mollamahmutoglu, Leyla (Gynecology Obstetrics & Reproductive Medicine, 2021)
OBJECTIVE: Despite the availability of better biomarkers, basal day 3 follicle-stimulating hormone is widely available and often used as the first-line test in ovarian reserve evaluation. The aim of this study was to evaluate the outcomes of cycles with elevated (>12 IU/mL) basal follicle-stimulating hormone values. STUDY DESIGN: Cycles with basal day 3 follicle-stimulating hormone values >12 IU/mL were divided into four cohorts according to follicle-stimulating hormone levels: group I, follicle-stimulating hormone between 12-15 IU/m, group II between 15-20 IU/mL, group III between 20-25 IU/mL and group IV >25 IU/mL. Both demographic characteristics and controlled ovarian stimulation parameters were retrospectively reviewed. RESULTS: Total antral follicle count was significantly higher in group I compared to the other three groups (p=0.001). Number of follicles ≥17 mm on human chorionic gonadotropin (hCG) day, number of retrieved oocytes, mature oocytes and fertilized oocytes were significantly higher in group I compared to the other groups (p=0.003, p=0.001, p=0.001, and p=0.001, respectively). No significant difference was found between groups regarding cancellation rates. The rate of embryo transfer per started cycle was significantly higher in group I compared to group III and group IV (p=0.001). Clinical pregnancy rates per embryo transfer were comparable among the groups. CONCLUSION: Despite the retrieval of lower quantities of oocytes, reasonable pregnancy rates could be achieved if embryo transfer was performed in cycles with follicle-stimulating hormone values over 12 IU/mL.